2015
DOI: 10.1093/jpids/piv028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Outcomes With Multiplex Molecular Testing of Stool From Children Admitted to Hospital With Gastroenteritis in Botswana

Abstract: Detection of bacterial enteropathogens is associated with increased mortality in children in sub-Saharan Africa. Unfortunately, most children with these infections do not have bloody stools, and bloody dysentery was not found to be associated with worse outcomes. Clinical trials evaluating outcomes associated with more aggressive diagnostic strategies in children presenting with severe acute gastroenteritis in sub-Saharan Africa should be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
(17 reference statements)
3
27
1
Order By: Relevance
“…The provision of antimicrobials is recommended only if blood is observed in the stools; this recommendation is probably linked to the assumption that the majority of children presenting with acute non-bloody diarrhoea are infected with viral pathogens, for whom no specific treatment is available. However, we have previously found that up to one-third of children in Botswana admitted to hospital without dysentery harboured a potentially treatable pathogen in their stool [7], and other investigators have observed similar findings in other low- and middle-income countries [8, 9]. Although it is not possible to reliably distinguish treatable bacterial or protozoal gastroenteritis from non-treatable gastroenteritis on clinical grounds in the absence of bloody stools, the use of rapid enteric diagnostics at the time of patient presentation could permit the use of targeted antimicrobial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of antimicrobials is recommended only if blood is observed in the stools; this recommendation is probably linked to the assumption that the majority of children presenting with acute non-bloody diarrhoea are infected with viral pathogens, for whom no specific treatment is available. However, we have previously found that up to one-third of children in Botswana admitted to hospital without dysentery harboured a potentially treatable pathogen in their stool [7], and other investigators have observed similar findings in other low- and middle-income countries [8, 9]. Although it is not possible to reliably distinguish treatable bacterial or protozoal gastroenteritis from non-treatable gastroenteritis on clinical grounds in the absence of bloody stools, the use of rapid enteric diagnostics at the time of patient presentation could permit the use of targeted antimicrobial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In our large (n=617) prospective study of community onset GE 15 where we also used a sensitive multiplex PCR assay, we detected at least one pathogen target in 83% of all children, which is a higher pathogen detection rate than we have found in these hospital associated cases described in this study. However, some of the leading pathogens detected in the community onset study were bacteria (e.g.…”
Section: Hospital-acquired Infection In Botswanacontrasting
confidence: 44%
“…Diarrheal illnesses, including rotavirus gastroenteritis, cause relatively high morbidity and mortality in Botswana in comparison with other African countries [20,21]. In July 2012, the Botswana Ministry of Health introduced a monovalent rotavirus vaccine (RV1; Rotarix) into its routine immunization program, recommending a 2-dose series at 2 and 3 months of age.…”
mentioning
confidence: 99%